Khali = Empty and me : a tale of friendship and loss - Mahdavi, Azam (Lee & Low Books, 2023)
"After a young girl's mother dies, Empty appears and silently takes up the big blank space left behind. For some time, the girl can't connect with her dad or any friends, and Empty is her closest companion. But then, a happy reminder of her mom pops up one day, and this bit of joy helps the little girl open up to the world around her. Empty stays around, but the little girl starts to connect with others and share new moments of happiness with them. Originally published in Iran, this bilingual Persian-English picture book provides a gentle starting point for discussing death and grief with young readers. Its spare, poignant text and artwork gives children a concrete point of reference for the complex emotions people experience after the loss of a loved one. Readers of any age, however, will find comfort in the encouraging message of this beautiful book" --